Predictive influence of personality traits on retirement anxiety among universities staff in Osun State, Nigeria - Joshua O Ogunsemi; Ebenezer O Akinnawo; Olusola I Akinbobola; Olutola O Olajire; Abayomi O Olusa; John L Okunola (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Retirement anxiety may occur in retirement-eligible staff, and their reaction may depend on their personality traits. This study examined the predictive influence of five-factor personality traits on retirement anxiety among non-academic staff in some selected universities in Osun State, Nigeria. MATERIALS AND METHODS: The study utilized a multistage sampling technique. Two self-administered instruments, Redeemer's University Retirement Anxiety Scale and Mini-International Personality Item Pool were completed by 463 non-academic staff in five selected universities in Osun State, Nigeria. Descriptive statistics (frequency and percentages) and inferential statistics (hierarchical regression, two-sample t-test, and one-way ANOVA) were used to analyze data. RESULTS: The study found a high prevalence rate of retirement anxiety (85.1%) among university staff in Nigeria. In all, 13%, 16%, and 12.5% of the participants showed high levels of retirement anxiety dimensions (personal obligation, financial planning, and social detachment), respectively. Sociodemographic and personality traits jointly accounted for statistically significant (16%, 29%, and 22%) changes in personal obligation (R2 =0.16, P <.01), financial planning (R2 =0.29, P <.01), and social detachment (R2 =.22, P <.01), respectively. Personality traits (extraversion, agreeableness, conscientiousness, and neuroticism) and socio-demographic variables (age, educational level, job tenure, and job status) jointly contributed to the prediction of retirement anxiety dimensions (obligation concerns, financial planning, and social detachment). CONCLUSION: The findings highlighted the need for psychosocial interventions targeting the at-risk population was highlighted.